2009
DOI: 10.1111/j.1529-8027.2009.00238.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving fatigue assessment in immune‐mediated neuropathies: the modified Rasch‐built fatigue severity scale

Abstract: Fatigue is a major disabling complaint in patients with immune-mediated neuropathies (IN). The 9-item fatigue severity scale (FSS) has been used to assess fatigue in these conditions, despite having limitations due to its classic ordinal construct. The aim was to improve fatigue assessment in IN through evaluation of the FSS using a modern clinimetric approach [Rasch unidimensional measurement model (RUMM2020)]. Included were 192 stable patients with Guillain-Barré syndrome (GBS), chronic inflammatory demyelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 19 publications
1
37
0
Order By: Relevance
“…Factor analysis of the FSS in the patient group demonstrated its unidimensional structure in MDD patients, in accordance with previous findings in other clinical groups [12,38,41] and in the general population [35]. Although the size of our sample was relatively small (less than 100 patients), many authors have suggested that a subjects-tovariables ratio of 5 or higher is sufficient, especially when inter-item correlations are high and the number of factors extracted is small [42,43].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Factor analysis of the FSS in the patient group demonstrated its unidimensional structure in MDD patients, in accordance with previous findings in other clinical groups [12,38,41] and in the general population [35]. Although the size of our sample was relatively small (less than 100 patients), many authors have suggested that a subjects-tovariables ratio of 5 or higher is sufficient, especially when inter-item correlations are high and the number of factors extracted is small [42,43].…”
Section: Discussionsupporting
confidence: 89%
“…In fact, ICC was found higher than values previously reported in other studies [8,12], possibly due to a shorter test-retest time interval. However, the 1-week interval, which has also been previously used [13,38], was selected in this study mainly on ethical grounds.…”
Section: Discussionmentioning
confidence: 99%
“…This would require evaluation of the clinimetric properties of these instruments. Moreover, because these instruments have non‐linear outcome measures, it would be advantageous if linear weighting could be applied, as done recently for the FSS for other immune‐mediated disorders ( van Nes et al, 2009 ) .…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these shortcomings, the Peripheral Neuropathy outcome measures Standardization (PeriNomS) study group has re-modeled the widely used FSS to a Rasch-built FSS, improving its concept and fulfilling modern clinimetric requirements in GBS and CIDP [14]. All future studies evaluating chronic conditions or conditions with chronic consequences should transform ordinal-obtained data to interval data using, for example, the Rasch method [15].…”
Section: Fatigue In Immune-mediated Neuropathiesmentioning
confidence: 99%